The role of dictionaries in memorizing and teaching Arabic Language The Unified Medical Dictionary as a Model - الأحمد, حسن; حسين الزعيّل العبد, عبد الباقي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research deals with the importance of Arabic dictionaries in defending the Arabic language and ensuring its integrity from the linguistic intruder of other languages. The common mistakes and linguistic hybrid which leads to the death and weakness of language, in addition to the big role played by dictionaries in the learning educational process especially if it is employed in the suitable way and invested in a real one. The research touched upon the great efforts and the special care that were made by other nations in the composition of general linguistic dictionaries and the linguistic dictionaries specialized in all fields of language's use such as the health, media, engineering, commercial, diplomatic and political sectors and others. There is no doubt that the health field is one of the most important fields in which the language is used, and one of the most fields in which language must be chosen carefully and accurately because errors occurs in the use of language and misunderstanding between the doctor and patient can lead to very bad results. Hence the research is presented to talk about the unified medical dictionary and its role in teaching the Arabic language to the members of health sciences, and the workers in health sector such as doctors, nurses, technicians and pharmacists because this segment is of great importance and how to benefit from this dictionary in teaching Arabic to this group of learners. The research concluded with a member of conclusions, recommendations and proposals.